Advances on gradient scaffolds for osteochondral tissue engineering. (14th May 2021) - Oliveira, Joaquim M; Ribeiro, Viviana P; Reis, Rui L
Abstract: The osteochondral (OC) tissue is one of the most hierarchical and complex structures known and it is composed by two main compartments of hyaline articular cartilage and subchondral bone. It exhibits unique cellular and molecular transitions from the cartilage to the bone layers. OC diseases such as osteoarthritis and traumatic lesions may affect the articular cartilage, calcified cartilage (interface region) and subchondral bone, thus posing great regenerative challenges. Tissue engineering (TE) principles can offer novel technologies and combinatorial approaches that can better recapitulate the biological OC challenges and complexity in terms of biochemical, mechanical, structural and metabolic gradients, and ultimately can provide biofunctional 3D scaffolds with high reproducibility, versatility and adaptability to each patient's needs, as it occurs in OC tissue defects. The recent reports and future directions dealing with gradient scaffolds for OCTE strategies are overviewed herein. A special focus on clinical translation/regulatory approval is given.